SUFFIX DERIVATIONAL DALAM NOVEL â€œTHE ONE AND ONLY IVANâ€ YANG DITULIS OLEH KATHERINE APLEGATE: Penelitian tentang morfologi - morfem - P.C Sudarmadi; Andreas Joris Sukamto (e-LinguaTera, 2022)
A novel written by Katherine Applegate entitled The One and Only Ivan contains so many derivational suffixes. Knowing suffixes could help the English learners enrich their vocabulary knowledge significantly. For the reason above, this research is aimed at. This research uses qualitative method as the research approach that it could help much in finding out the meaning of derivational suffixes and the functions of each derivational suffix. The data of this study are in the form of words which contain English suffixes. The data is collected by downloading The One and Only Ivan novel from internet, and by reading the entire source of the data. To analyze the data, the writers use Plag theory (2002) to sort the suffixes into their categories. After that, the writers classify, and analyze the data as the procedures of data analysis. Finally, the writers take the conclusion. In this novel, there are four types of suffixes. The suffixes found are nominal suffix, adverbial suffix, adjectival suffix, and verbal suffix. The suffixes found in this novel are -ness, -ion, -ation, -ful, -er, -ance, -ence, -ment, -or, -ity, -ty, -ly, -y, -able, -ic, -ive, -en, -ful, -en. All of the suffixes may form other words class from the root word or change the meaning of the words, though not all of them are analyzed completely because of the space limitation.